Changes in Clear‐Sky Shortwave Aerosol Direct Radiative Effects Since 2002. Issue 5 (11th March 2021) - Loeb, Norman G.; Su, Wenying; Bellouin, Nicolas; Ming, Yi
Abstract: A new method for determining clear‐sky shortwave aerosol direct radiative effects (ADRE) from the Clouds and the Earth's Radiant Energy System is used to examine changes in ADRE since 2002 alongside changes in aerosol optical depth (AOD) from the Moderate Resolution Spectroradiometer. At global scales, neither ADRE nor AOD show a significant trend. Over the northern hemisphere (NH), ADRE increases by 0.18 ± 0.17 Wm −2 per decade (less reflection to space) but shows no significant change over the southern hemisphere. The increase in the NH is primarily due to emission reductions in China, the United States, and Europe. The COVID‐19 shutdown shows no noticeable impact on either global ADRE or AOD, but there is a substantial influence over northeastern China in March 2020. In contrast, February 2020 anomalies in ADRE and AOD are within natural variability even though the impact of the shutdown on industry was more pronounced in February than March. The reason is because February 2020 was exceptionally hot and humid over China, which compensated for reduced emissions. After accounting for meteorology and normalizing by incident solar flux, February ADRE anomalies increase substantially, exceeding the climatological mean ADRE by 23%. February and March 2020 correspond to the only period in which adjusted anomalies exceed the 95% confidence interval for 2 consecutive months. Distinct water‐land differences over northeastern China are observed in ADRE but not in AOD. This is likely due to the influence of surface albedo on ADRE in the presence of absorbing aerosols. Key Points: Satellite observations show that radiative cooling by aerosols has significantly declined over North America since 2002 During the COVID‐19 shutdown, hot and humid conditions over northeastern China masked the influence of reduced aerosol emissions After accounting for meteorology, aerosol radiative cooling over northeastern China is reduced by up to 23% in early 2020